Green biosynthesis of nanoparticles : mechanisms and applications (CABI, 2013)
This book presents the green synthesis of nanoparticles by algae, diatoms, bacteria and plants, and discusses the mechanisms behind the synthesis of nanoparticles. The book should be immensely useful for students, researchers and teachers of biology, chemistry, chemical technology, nanotechnology, microbial technology and those who are interested in green nanotechnology.